2022
DOI: 10.3390/ma15030811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vibration Modes and Wave Propagation of Operational Rails by Multipoint Hammering and Reciprocity Theorem

Abstract: Vertical bending vibration modes and rail wave propagation, including the damping characteristics, are the factors that cause rail corrugation. However, the ability to identify actual railways has been limited because of the huge number of sensors required for field tests. In this study, a novel and field-applicable method for identifying rail vibration modes and wave propagation characteristics is developed by multipoint hammering and the reciprocity theorem instead of multipoint measuring. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…An accelerometer is a typical sensor that can be applied as a vibration/ seismic sensor; it can sense ground vibration [15]. Some researchers utilized it for various aims, such as a laboratory scale measurement to calculate the physical property of the materials [16], sedimentary rocks [17], or igneous/ metamorphic rocks [18], and in situ elastic properties investigation through the wave propagation in the geotechnical field [19,20]. A geophone can also be occupied as a vibration sensor, yet, the frequency response is less than in an accelerometer [21].…”
Section: Introductionmentioning
confidence: 99%
“…An accelerometer is a typical sensor that can be applied as a vibration/ seismic sensor; it can sense ground vibration [15]. Some researchers utilized it for various aims, such as a laboratory scale measurement to calculate the physical property of the materials [16], sedimentary rocks [17], or igneous/ metamorphic rocks [18], and in situ elastic properties investigation through the wave propagation in the geotechnical field [19,20]. A geophone can also be occupied as a vibration sensor, yet, the frequency response is less than in an accelerometer [21].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the existing methodologies for the conduction of experiments utilized in the verification and validation of rail track elements and structures, and in the investigation of the influential issues of rolling stock on rail tracks [6][7][8][9][10][11], has suggested that the concepts and ideas about the process to be measured, based on the theoretical fundamentals of determining strength, stability, and fatigue strength [12][13][14][15][16][17][18][19], are the determining factors during the setup of an experiment. These properties of the elements and structures determine their suitability for their intended functions under the defined operating conditions and the maintenance system.…”
Section: Introductionmentioning
confidence: 99%